Daily identity practices: Belarus and potato eaters. Issue 2 (June 2019) - Zadora, Anna
Abstract: Food cultivation, preparation and consumption are important references for shaping national identity. Food is a crystallization of the history of a national or ethnic group, of its traditions, mentality, and religious adherence and of very pragmatic material elements reflecting the way of life of the group, for instance, climatic conditions and socio-economic levels. All elements of the history of a group are transmitted and experienced in daily rituals relating to food. Food has strong symbolic, quasi-sacred associations in many cultures: for Slavic peoples bread is a very important symbol, and in Belarus potatoes are known as "the second bread". The role played by banal everyday identity rituals is very important in complex political contexts, where identity building processes aimed at the transformation of a community into a nation-state with common identification denominators are not endorsed by political elite. Belarus is an extremely difficult case from the point of view of identity building: a country without a history (Zaprudnik, 1993 ), without a nation (Marples, 1999), without an identity (Bekus, 2010). In the Belarusian context, food - especially food which is cheap, rustic and simple to cultivate, such as potatoes - is an important identity marker.